PENGARUH SUASANA TOKO DAN CITRA TOKO TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN PADA TOKO BUKU RAMEDIA DI KOTA PALU - Dwitama, Andhika (Fakultas Ekonomi Universitas Tadulako, 2016)
The purpose of this study is to know and analyze the influence of store atmosphere (X1) and store image (X2) simultaneously and partially significant effect on purchasing decision of consumer (Y) at Bookstore Ramedia in Palu City. This type of research is causal research. The population of this study is the people of Palu City who were / were buying at Ramedia Bookstore. Sampling technique using purposive sampling with sample number 90 people. The analysis tool used is multiple linear regression analysis. Based on the result of multiple linear regression analysis, it was found that store atmosphere variables (X1) and store image (X2) simultaneously significant influence consumer purchasing decision(Y) at Ramedia Bookstore in Palu with significant value 0.001 below <0.05. Store atmosphere variables (X1) = 0.021 and store image (X2) = 0.042 partially significant effect on purchasing decision of consumer in Ramedia Bookstore in Palu City.